Pengaruh Kualitas Pelayanan dan Biaya Administrasi Terhadap Kepuasan Nasabah Tabungan Faedah Pada BRI Syariah Cabang Banda Aceh - Yulindawati; Ridla Tarigan, Ismail Rasyid; Ferdian, Aan Muhammad (Scientific Journal of Students Islamic Economics and Business, 2022)
This study was conducted to determine the effect of the influence of service quality and administrative costs on customer satisfaction. The study at BRI Syariah Kc Banda Aceh. This research method uses quantitative methods with data collection techniques through distributing questionnaires to 100 respondents, namely Tabungan Faedah customers. The results showed that: (1)Service quality had a positive and significant effect on customer satisfaction at Bank BRI Syariah KC Banda Aceh. (2)Administrative costs have a positive and significant effect on customer satisfaction at Bank BRI Syariah KC Banda Aceh. (3)Service Quality and Administration Costs simultaneously have a significant effect on customer satisfaction